The Effect of Individual Counseling to Enhance Self-Esteem of Depression Patients at Songkhla Rajanagarindraphychiatic Hospital in Songkhla Province - เงารังษี อารี; วงษ์ทิม สุขอรุณ; เมฆขจร นิธิพัฒน์ (Journal of The Royal Thai Army Nurses, 2019)
This This study aimed to (1) compare the levels of self-esteem of depression patients in the experimental group before and after receiving individual counseling; and (2) compare the level of self-esteem of depression patients in the experimental group who received individual counseling with that of depression patients in the control group who received normal care.The research sample consisted of 14 depression patients who came to receive treatment at Songkhla Rajanagarindra Psychiatric Hospital, obtained by purposive sampling technique. Then, they were randomly divided into 2 groups, the experimental group and the control group, with 7 patients in each group. The experimental group received individual counseling for 8 sessions, each of which lasted for 50 minutes. The research instruments were (1) a scale to assess self-esteem, with reliability coefficient of .91; and (2) an individual counseling program for developing self-esteem. The employed statistics for data analysis were the median, inter-quartile range, Wilcoxon Matched Pairs Singed-Ranks Test and Mann-Whitney U Test. The results showed that (1) the post-experiment self-esteem level of depression patients in the experimental group who received individual counselling was significantly higher than their pre-experiment counterpart level at the .01 level of statistical significance; and (2) the post-experiment self-esteem level of depression patients in the experimental group who received individual counselling was significantly higher than the counterpart level of depression patients in the control group who received normal care at the .01 level of statistical significance.